[PROVISIONAL] Low cytomolecular diversification in the genus Stylosanthes Sw. (Papilionoideae, Leguminosae) - Ana Luiza Franco; Amanda Figueredo; Lívia de Moraes Pereira; Saulo Marçal de Sousa; Gustavo Souza; Marcelo Ayres Carvalho; Marcelo F. Simon; Lyderson Facio Viccini (Genetics and Molecular Biology)
Abstract Stylosanthes (Papilionoideae, Leguminosae) is a predominantly neotropical genus with ~ 48 species that includes worldwide important forage species. This study presents the chromosome number and morphology of eight species of the genus Stylosanthes (S. acuminata, S. gracilis, S. grandifolia, S. guianensis, S. hippocampoides, S. pilosa, S. macrocephala and S. ruellioides). In addition, staining with CMA and DAPI, in situ hybridization with 5S and 35S rDNA probes, and estimation of DNA content were performed. The interpretation of Stylosanthes chromosome diversification was anchored by a comparison with the sister genus Arachis and a dated molecular phylogeny based on nuclear and plastid loci. Stylosanthes species showed 2n = 20, with low cytomolecular diversification regarding 5S rDNA, 35S rDNA and genome size. Arachis has a more ancient diversification (~ 7 Mya in the Pliocene) than the relatively recent Stylosanthes (~ 2 Mya in the Pleistocene), and it seems more diverse than its sister lineage. Our data support the idea that the cytomolecular stability of Stylosanthes in relation to Arachis could be a result of its recent origin. The recent diversification of Stylosanthes could also be related to the low morphological differentiation among species, and to the recurrent formation of allopolyploid complexes.